Long-term records of hard-bottom communities in the southwestern Baltic Sea reveal the decline of a foundation species. (5th April 2019) - Franz, Markus; Barboza, Francisco Rafael; Hinrichsen, Hans-Harald; Lehmann, Andreas; Scotti, Marco; Hiebenthal, Claas; Molis, Markus; Schütt, Renate; Wahl, Martin
Abstract: Ecological processes modulate ecosystem functioning and services. Foundation species are those exerting intense control on such processes as both their existence and loss have profound implications on the structure of ecological communities. For the distinction between random fluctuations and directional regime shifts in community composition, long-term records are of strategic need. In this study we present the monitoring of benthic hard-bottom communities over 11 years along seven stations in the SW Baltic Sea. Regional differences were found between the communities of Kiel and Lübeck bights, with the former area displaying signs of regime shift. The decline and near disappearance of the foundational species Mytilus edulis from settlement panels deployed in Kiel Bight correlated with three environmental variables: sea surface temperature, water current speed and chlorophyll a concentration. Thus, low spring temperatures, in some cases reinforced by local maxima of chlorophyll a, correlated with reduced recruitment of Mytilus . Moreover, regional differences of larval dispersal and population connectivity could explain the rapid recovery after disturbance of the mussel populations in Lübeck Bight in contrast to Kiel Bight. Our findings underscore the relevance of long-term monitoring programmes to detect the interactive impacts of global climatic and regional environmental drivers. Graphical abstract: Image 1 Highlights: Records of hard-bottom communities show regional differences in community dynamics. Regionally, signs of regime shift were detected. Shift can be explained by the decline of the foundation species Mytilus sp. Modelling process revealed three environmental variables explaining the decline. Regional differences in larval dispersal could explain contrary Mytilus recoveries.